Интеллектуальный капитал как важный фактор повышения конкурентоспособности предприятия - Брюховецкий, Я.С. (Стратегія і механізми регулювання промислового розвитку, 2014)
Рассмотрены теоретические и практические аспекты формирования и реализации интеллектуального капитала. Раскрыта роль интеллектуального капитала в обеспечении конкурентоспособности отечественных предприятий на современном этапе экономического развития. Обоснованы предложения по более полному использованию интеллектуального капитала отечественными предприятиями. Розглянуто теоретичні та практичні аспекти формування і реалізації інтелектуального капіталу. Розкрито роль інтелектуального капіталу в забезпеченні конкурентоспроможності вітчизняних підприємств на сучасному етапі економічного розвитку. Обґрунтовано пропозиції щодо більш повного використання інтелектуального капіталу вітчизняними підприємствами. The theoretical and practical aspects of the formation and implementation of intellectual capital. The role of intellectual capital in ensuring the competitiveness of domestic enterprises at the present stage of economic development. Indicated by the results of the use of the characteristics of enterprises intellectual capital. Stages of the financial management of the intellectual capital of the enterprise. The prospects for further research in the field of intellectualization enterprises. Substantiated proposals for fuller use of the intellectual capital of domestic enterprises.